A first report on the synthesis of a complex of unsubstituted 1, 2, 3-triazolo[1, 5-a]pyridine formed in situ via oxidative N–N bond coupling: Structural, photoluminescent, and biological properties of a new Cu(II) complex and its use as a single-source precursor for Cu and CuO nanoparticles. (January 2021) - Sathiyakumar, Subramani; Selvam, Pitchai; Radhika, Jayaraman; Antharjanam, Sudhadevi; Hakkim, Faruck Lukmanul; Srinivasan, Krishnan; Premkumar, Thathan
Abstract: New copper(II) complexes [Cu(Pytc)(Cl)2 ]·2H2 O (1 ) and [Cu2 (tzp)2 (CH3 COO)4 ] (2 ) (Pytc =  tert -butyl 2-(pyridine-2yl-methylene)hydrazinecarboxylate; tzp = 1, 2, 3-triazolo[1, 5- a ]pyridine) were prepared and were characterized by elemental analysis, electron impact mass spectrometry, UV–visible spectroscopy, infrared spectroscopy, and photoluminescence studies. A single-crystal X-ray diffraction study of 2 revealed a paddle-wheel copper(II) acetate structure with tzp acting as a monodentate ligand coordinated axially. Pytc and the metal complexes showed emissive, antibacterial, and antifungal properties. Furthermore, 2 was demonstrated to be a solid-state single-source precursor to form Cu and CuO nanoparticles (NPs) under different atmospheric conditions. By transmission electron microscopy, the as-prepared nanoparticles were observed to be roughly spherical with average particle sizes of approximately 10–12 nm for Cu NPs and approximately 20–22 nm for CuO NPs. Furthermore, high crystallinity, high purity, and the single-phase nature of the as-prepared NPs were revealed by the powder X-ray diffraction pattern. Graphical abstract: The synthesis of an unsubstituted 1, 2, 3-triazolo[1, 5- a ]pyridine (tzp)–metal complex, in particular an unsubstituted tzp–copper(II) acetate complex, is reported. Taken together, the ability to prepare both metal (Cu) nanoparticles (NPs) and metal oxide (CuO) NPs through a solid-state single-source precursor with a new tzp–copper(II) acetate complex and the demonstration of the solid-state emission properties and antibacterial and antifungal potential of the complex make this system a new platform for industrial and biomedical applications. Pytc, tert -butyl 2-(pyridine-2yl-methylene)hydrazinecarboxylate. Image 1 Highlights: A new Schiff base to act as a ligand has been prepared by solvent-free methods. An unsubstituted 1, 2, 3-traizolo[1, 5- a ]pyridine–copper(II) acetate complex has been synthesized. The complex was used as a solid-state single-source precursor to prepare Cu and CuO nanoparticles.